Food security and dietary diversity patterns amongst female handloom workers: a cross sectional study from Kerala, India - Devika Nair; Arti Muley (Discover Food, 2024)
Abstract Introduction The onset of COVID-19 in December 2019 bought the entire world to a standstill and had a major impact on the social and economic sectors in India. One of the most affected groups in this pandemic has been the female handloom workers. Purpose The purpose of this study was to assess food security and dietary diversity amongst female handloom workers in Kerala. Methods After obtaining informed consent, data was collected from 140 respondents working in handloom cooperative societies across Ernakulum, Kerala. Data regarding the food security and dietary diversity status of female handloom workers were collected using the validated Household Food Insecurity Access Scale and the Individual Dietary Diversity Scale respectively. Descriptive statistics was used to calculate the mean, standard deviation, frequency, and percentage while the independent t-test and Chi-Square test were used to compare means and examine the relationship between continuous and categorical variables respectively. Results The mean age of the respondents was reported to be 53.69 ± 8.39. Majority of the respondents (91.4%) had co-morbidities with the most prevalent one being occupational hazards (45.7%). 96.4% and 53.5% of respondents were found to be food insecure and have poor dietary diversity respectively. In unadjusted analyses, statistical relationships were found between several variables and food security status, like milk and milk products (p = 0.045), flesh meats (p = 0.007), and history of disease and limited variety of foods due to lack of resources (p = 0.003). A strong relationship was also established between receiving extra rations through the Pradhan Mantri Garib Kalyan Yojana and food security status (p = 0.002). Conclusion The results revealed the bleak state of nutrition in the community. Further research into their nutritional knowledge, attitudes and practices needs to be carried out to recognize efficient variables for comparison from an Indian context.